1999
DOI: 10.1002/(sici)1521-3765(19991001)5:10<3066::aid-chem3066>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of 2-Aminophenylpalladium(II) Complexes: Insertion Reactions of Oxygen and Carbon Monoxide into Carbon−Palladium Bonds—New Examples of “Transphobia”

Abstract: Abstract:Mixtures of ªPd(dba) 2 º (dba dibenzylideneacetone) and neutral ligands react with an excess of 2-iodoaniline to give [Pd(C 6 H 4 NH 2 -2)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
119
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(142 citation statements)
references
References 28 publications
22
119
1
Order By: Relevance
“…The relative cis-arrangement of the phosphines was found in [Rh(L) 2 ][BF 4 ] (4). These observations are also consistent with previous literature reports, which suggested that the mutual trans positioning (in square planar complexes) of two phosphorous ligands, or of a phosphorus and a carbon ligand, would lead to the weakening of the corresponding M-P bonds[71,82].…”
supporting
confidence: 56%
“…The relative cis-arrangement of the phosphines was found in [Rh(L) 2 ][BF 4 ] (4). These observations are also consistent with previous literature reports, which suggested that the mutual trans positioning (in square planar complexes) of two phosphorous ligands, or of a phosphorus and a carbon ligand, would lead to the weakening of the corresponding M-P bonds[71,82].…”
supporting
confidence: 56%
“…[13,14] A second ionic species is then generated in a subsequent reaction. This latter might be a decarbonylation as in Equation (10) or any decomposition process leading to more conductive ionic species {e.g., formation of a phosphonium salt PhCOO-PPh 3 ϩ via a reductive elimination from [(PhCO)Pd(OCOPh)(PPh 3 ) 2 ], [15] reaction of dioxygen with [(PhCO)PdS(PPh 3 ) 2 ] ϩ , [16] etc.}. …”
Section: Palladium(ii) Complexes Generated In the Oxidative Addition supporting
confidence: 91%
“…Consequently, one equiv. (16)]. [24] Such a complex did not appear when PPh 3 was exchanged by dppp in Scheme 1.…”
Section: O (Experiments a And B Table 2 Entry 3) When Phcomentioning
confidence: 99%
“…Arylpalladium complexes tend to coordinate hard ligands in a position trans to the PdϪC(aryl) bond and to avoid coordination of soft ligands. This fact has been reported as transphobia, [14,15] and is followed in trans-[PdAr(NHPh)(PMe 3 ) 2 ]. [8] In complex 1 the hard N(amido) ligand arranges cis to the PdϪC(aryl) bond, leaving the softer ligand chloro in trans position to the PdϪC(aryl) bond.…”
Section: Methodsmentioning
confidence: 99%